Predicting Future Identity of English For Young Learner (EYL) Teachers: Investigating How Coursework Shapes Pre-Service Teachers' Identities and Teaching Readiness - Santi Farmasari; Lalu Ali Wardana; Baharuddin; Hartati Suryaningsih (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: Research on English language teacher education has largely emphasized practicum experiences in shaping professional identity and teaching readiness. However, limited attention has been given to how coursework in English for Young Learners (EYL) programs contributes to early identity formation. This gap warrants closer empirical examination Methodology: A total of 121 students enrolled in EYL courses were invited to participate, and 50 of them gave their consent. Data were collected through reflective journals and a Likert-scale questionnaire. Findings: Thematic analysis revealed four recurring themes: evolving teacher identity, teaching readiness, impactful coursework components, and aspirations for future practice. Quantitative findings supported these insights, with a strong correlation found between meaningful coursework experiences and students’ visions for their future classrooms. While many participants felt intellectually prepared, some expressed concerns about emotional readiness, underscoring the need for supportive, hands-on learning environments. Conclusion: The study concludes that coursework has formatively built not only the pre-service teachers’ skills, but also a strong and sustainable sense of who they are and hope to be as future EYL educators. Originality: Grounded in English for Young Learners pedagogy, this study foregrounds coursework as a critical site of early professional identity formation for pre-service EYL teachers. Moving beyond practicum-centered ELT research, it provides mixed-method evidence of how child-centered, play-based, and reflective coursework shapes identity, teaching readiness, and future classroom enactment in an EFL context.